Pengaruh website quality terhadap perceived trust dan dampaknya pada repurchase intention pada website Matahari Mall - Sudiyono, Freddy; Chairy, Chairy (Jurnal Manajemen Bisnis dan Kewirausahaan, 2017)
The purpose of this study was to determine the effect of website quality on perceived trust and its impact on repurchase intention with website brand and perceived value as the moderate variables. This is an explanatory type of research, using a partial least square (SEM-PLS) analysis technique which is measured with the help of SmartPLS 3.0 software. The data collection method is by distributing questionnaires with probability sampling techniques taken from the unknown population of Matahari Mall website visitors, questionnaires were distributed from May to August 2017 so that been collected the number of 100 respondents who deployed in May 2017. The results of this study indicate a significant and positive direct effect of website quality and perceived trust on the repurchase intention of the Matahari Mall website. Perceive value also has a significant impact on moderating the relationship between perceived trust and repurchase intention. Moreover, website quality has the biggest impact directly on repurchase intention. Advice given to the Matahari Mall website is firstly to improve website quality through product content and description evaluation and make the rules for business partners about the standard of product content and description information, and also, they have to improve the supervision of website content and description information.